A Transition to a Net Oil Importir Country - Masfar Gazali (Universitas Trisakti, 2005)
Indonesia is becoming a net oil impoter in the near future. due to increasing domestic need of petroleum while on the other hand the exporting activity of crude oil is inevitable. Indonesia is buying the higher price and selling at the lower, and spending the more valuable to get the less. This paper examines the contradictory situation and its implication to Indonesia's terms of trade and gives a methodical evaluation of supply and demand scale for domestic market in the future. To resolve this problematic issue, a key policy is suggested to be applied namely